Increasing opportunities for community input in harm reduction program development using iterative engagement - Wagner, Nicole M.; Carlson, Jordan A.; Bean, Meagan; Wineland, Amy; Blum, Joshua; Cardona, Scott A.; Covarrubias, Sheila; Kempe, Allison; King, Abby C.; Huebschmann, Amy G. (Harm reduction journal, 2025)
Background Incorporating people who use substances into a community-engaged research process can support the implementation and evaluation of evidence-based harm reduction programs. Attending to their voice ensures those who need these programs will use them. Yet, ongoing co-learning with people who use substances, often the ideal for community engaged research, poses a challenge for recruitment, ongoing participation, and obtaining diverse perspectives. We need novel strategies to support flexibility among populations experiencing legal and social instability so that community engaged work includes more diverse perspectives. In this paper, we describe a novel community engagement approach called Effective Adaptable and Sustainable in Your Community: Operationalizing Program Sustainability (EASY OPS). EASY OPS uses iterative engagement with people with lived/living substance use experience to design and implement harm reduction vending machine and kiosk programs, aiming to increase program use in those who would benefit most. Main body The EASY OPS approach addresses two key challenges to access and use of evidence-based harm reduction programs in underrepresented populations: (1) the need for attention to elements of the environment, and (2) ways to navigate challenges to ongoing research collaboration with community members experiencing substance use disorders. EASY OPS uses walking interviews with participants to identify environmental factors contributing to perceived use of services. Iterative engagement with community members–through interviews, surveys, and focus groups–was conducted to inform program development from the community’s perspective as feasibility challenges emerged. Conclusions This paper describes the novel EASY OPS strategy that facilitates iterative community engagement for harm reduction research and program development to better tailor implementation to the needs of diverse populations with lived/living experience. The potential impact is to reduce disparities by enhancing representative reach and access to substance use service and harm reduction programs.